Anatomical variations of brachial plexus: anomalous branching pattern - Gopal, Krishna; ., Anurag; Singh, Onkar (International Journal of Research in Medical Sciences, 2017)
Background: The brachial plexus is the plexus of nerves formed by the anterior rami of lower four cervical and the first thoracic spinal nerves with little contribution of prefix C4 and postfix T2 spinal nerve. The variations in formation, location, and courses of the cords of brachial plexus and the median nerve are not uncommon and were studied in both axillae. Methods: The forty cadavers were studied preserved in the department of anatomy, SGRRIM and HS, Dehradun. The age and sex of the cadavers were not taken into consideration. The upper limbs were examined for the abnormal formation and union of branches of brachial plexus. Results: The musculocutaneous nerve communicates with the median nerve before and after piercing the coracobrachialis muscle. The lateral cord also gives the twig to the both roots of the median nerve. It also gives a branch which joined the ulnar nerve. The communication between medial root of median nerve and ulnar nerve also observed. Conclusions: Out of 20 examined cadavers (forty upper limbs), the variations in the formation and distribution of branches of the brachial plexus were noted in nine limbs (22.5%). The both sides of the brachial plexus were inspected and it was not found bilateral variations even in a single cadaver. The knowledge of these variations may be helpful for the anatomists, radiologists, anaesthetist, neurosurgeons and orthopaedic surgeons during surgical operation of the upper limb.